Review on solution methods for random vibration problems - Faris Fekry, Waleed; Daoud, Jamal Ibrahim (INSI Publications, 2011)
Random vibration is becoming more and more important for many applications. It poses a serious challenge to the researchers because of its complex nature. In this paper we tried to classify the existing random vibration solution techniques and explain them in clear manner that will help any researcher in the future to apply the right approach for the right problem.